HVDC Bridge Generator Feeded by a Current Source From Series Resonant Converter - Tonmitra, Kitipong; Addoddorn, Chaiporn; Suksri, Amnart (Engineering and Applied Science Research, 2015)
This paper presents the design and construction of HYDC bridge generator by using voltage multiplier bridge type comprising of 2 stages feeded by a current source from series resonant converter rated at 15 kHz, 40 kY 5 rnA. This HYDe generator has improved the voltage drop in the circuit which is better than the case of HYDC generator operation at 15 kHz without series resonant converter. From the simulation test based on TINA simulator, it confirms that at the frequency of 15 kHz with the series resonant converter, has produced higher voltage than the conventional HYDC generator at 15 kHz that does not use the series resonant of 61 0 Y at 2 stages, 900 Y at 3 stages and 1.43 kYat 4 stages respectively. In the actual tests and simulations results have been shown to agree well with the designed while HYDC generator have resulted to a less voltage drop than the conventional HYDC generator at equal input voltage.